2021
DOI: 10.35784/acs-2021-08
|View full text |Cite
|
Sign up to set email alerts
|

Plant Classification Based on Leaf Edges and Leaf Morphological Veins Using Wavelet Convolutional Neural Network

Abstract: The leaf is one of the plant organs, contains chlorophyll, and functions as a catcher of energy from sunlight which is used for photosynthesis. Perfect leaves are composed of three parts, namely midrib, stalk, and leaf blade. The way to identify the type of plant is to look at the shape of the leaf edges. The shape, color, and texture of a plant's leaf margins may influence its leaf veins, which in this vein morphology carry information useful for plant classification when shape, color, and texture are not not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Neural networks (NN) are computing systems inspired by the biological neural networks (Kohonen, 1982), which learn to solve tasks by considering examples without being programmed with any specific rules. The neural networks were applied to solve the variety of classification tasks in (Alyamani & Yasniy, 2020;Dewi & Utomo, 2021;Sridharan et al, 2021). The training of neural networks can be achieved in several ways, using, for instance, the approach called particle swarm optimization that was employed in (Al-Awad, Abboud & Al-Rawi, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Neural networks (NN) are computing systems inspired by the biological neural networks (Kohonen, 1982), which learn to solve tasks by considering examples without being programmed with any specific rules. The neural networks were applied to solve the variety of classification tasks in (Alyamani & Yasniy, 2020;Dewi & Utomo, 2021;Sridharan et al, 2021). The training of neural networks can be achieved in several ways, using, for instance, the approach called particle swarm optimization that was employed in (Al-Awad, Abboud & Al-Rawi, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Their findings showed that their method performed better than cutting-edge techniques, with an accuracy of 97.58% on the set of images for rice pests and diseases (Shao et al, 2021) proposed a method that merges the LC-FCN model based on pretrained models with the watershed algorithm for dense rice image recognition with an accuracy of 89.88% DAWI and Wulan propose research doing a method using wavelets to denoise the images of the data set and then performs the classification of these images with convolution method. The results obtained using the wavelet method and convolutional neural network gave an accuracy of 97% (Dewi and Utomo, 2021;Yu et al, 2019) and propose a new approach for the detection of apple leaf diseases using deep learning considering regions of interest. They designed two sub-networks in the first step.…”
Section: Introductionmentioning
confidence: 97%
“…Lecturers are also required to have the ability to identify plants to assist lecturers in providing students with an understanding of plant taxonomy. Of course, this ability must be adapted to developments in the digital era (Dewi & Utomo, 2021;Kala & Viriri, 2018). The development of science and technology in the field of education is a challenge to create learning media that can assist the learning process to improve the quality of education.…”
Section: Introductionmentioning
confidence: 99%